ANALISIS KUALITAS PELAYANAN RUMAH SAKIT ‘AISYIYAH PARIAMAN TERHADAP KEPUASAN PESERTA JKN (JAMINAN KESEHATAN NASIONAL) - Lubis, Zaky Mubarak; R, Siti Hanafiah (IAIN Batusangkar, 2020)
This research is a quantitative study, which aims to analyze services quality to the satisfaction of inpatient JKN participants at Aisyiyah Hospital, Pariaman. This research was conducted on July to August 2019 by using a survey design. The sample was 100 patients taken by applying purposive sampling techniques. Data were analyzed through servqual method and IPA analysis. The research results showed overall services dimension, between services provided by ?Aisyiyah Pariaman Hospital and patient expectations, shows a gap of 2,308. This score was categorized in a high group which means the service is already good. It was based on importance analysis in quadrant A (physical evidence, empathy, and guarantee); in quadrant D (a reliability dimension); and in quadrant C (a responsiveness dimension).